Marginalisasi Hukum Adat pada Masyarakat Adat The marginalization of adat law on adat communities - Suartina, Tine (Jurnal Masyarakat dan Budaya, 2025)
his paper attempts to see adat and adat law marginalizations, and the implications on adat peoples. In Indonesia, despite the recognition for adat peoples in the Constitution and formal rules, including adat institutions, in practice there has been a long-term marginalization. The inconsistent State’s policies towards the adat law application play a role in the marginalization of adat communities at various levels. Having field research in Ciptagelar, Karang and Guradog kasepuhan communities in western Java and legal pluralism perspective, this paper elucidates the lack of adat law recognition giving certain impacts on adat peoples, including on their social lives and livelihood. This study also proves that although adat law is not practically adopted by the State, in some cases, adat peoples find strategies to maintain their beliefs and adat law. Thus, in a broader context, the marginalization is unable to eliminate adat and adat law as a whole. To date the practice of multi-legal systems in a plural society, such as Indonesia, still takes place, both in conflict and coexistence. Moreover, in discussing Indonesia’s implementation of law from a community perspective, the distinction between formal and informal systems is still needed and legal unification only functions within certain limits